2010
DOI: 10.5194/adgeo-26-71-2010
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian trend analysis for daily rainfall series of Barcelona

Abstract: Abstract.A Point-Over-Threshold approach using a reparameterization of the Generalized Pareto Distribution (GPD) has been used to assess changes in the daily rainfall Barcelona series . A Bayesian approach, considering the suitable scale and physical features of the phenomenon, has been used to look for these alterations. Two different models have been assessed: existence of abrupt changes in the new GPD parameters due to modifications of the observatory locations and trends in these GPD parameters, pointing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The illustration series in this contribution shows no overlap between model hindcast and measured data, and therefore the proposed model does not account for it. An analogous model for overlapping series was presented by Ortego et al (2012), where it was shown that the results are not significantly altered when accounting for overlap, albeit for significant wave height data.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The illustration series in this contribution shows no overlap between model hindcast and measured data, and therefore the proposed model does not account for it. An analogous model for overlapping series was presented by Ortego et al (2012), where it was shown that the results are not significantly altered when accounting for overlap, albeit for significant wave height data.…”
Section: Introductionmentioning
confidence: 91%
“…where, for simplicity, {t i }, {τ j } represents all available data on elapsed times between consecutive events. When interruptions of observations are present, as is the case in the buoy data set, some time differences τ j − τ j −1 do not correspond to elapsed times between consecutive events; these time intervals are ignored in the likelihood (see further details in Ortego et al, 2012), i.e. the likelihood (Eq.…”
Section: Occurrence Of Wind Eventsmentioning
confidence: 99%
“…By the same token, modification of human activities should be considered as an important task for the improvement of flood management. Focusing on another Spanish region (in this case, the coast of Alicante), Olcina Cantos et al (2010) analyze the increased exposure and vulnerability to floods as a result of a major urban occupation of areas that are subject to this hazard, in spite of the existence of flood risk prevention plans. Survey-based research in the areas affected by the most recent episodes reveals a lack of awareness for a large portion of the population, which is particularly evident for the seasonal inhabitants or residents who have not lived in the area for very long.…”
Section: Published By Copernicusmentioning
confidence: 99%
“…As a result, these assessment studies may be highly dependent on the methodologies and data that are used to analyze trends and anomalies, while analyses for different time periods may give different results and lead to ambiguous conclusions. This is the case for the papers by Neppel et al (2011), which deals with a multivariate regional test for the detection of trends in extreme rainfall, and by Ortego et al (2010), which focuses on the application of the Bayesian analysis to detect potential trends in daily rainfall series.…”
Section: Climate Change Impacts On Mediterranean Stormsmentioning
confidence: 99%
“…In order to take into account the restriction ξ < 0, other parameterisations of GPD in the Weibull domain of attraction have been proposed (Ortego et al, 2010(Ortego et al, , 2012; we adopt here the parameterisation in Ortego et al (2012). We use…”
Section: Event Magnitude Modelmentioning
confidence: 99%